Sjögren-Larsson syndrome: report of monozygote twins and a case with a novel mutation - Yiş, Uluç; Terrinoni, Allesandro (The Turkish Journal of Pediatrics, 2012)
Sjögren-Larsson syndrome is an autosomal recessive neurocutaneous disease caused by mutations in the ALDH3A2 gene for fatty aldehyde dehydrogenase, a microsomal enzyme that catalyzes the oxidation of medium- and long-chain aliphatic aldehydes fatty acids. We studied three Turkish Sjögren-Larsson syndrome patients with ichthyosis, developmental delay, spastic diplegia, and brain white matter disease. One patient was homozygous for a novel ALDH3A2 mutation in exon 5. The mutation involves the codon 228 (CGC) with the transversion G->A modifying the codon in CAC, leading to the substitution of the original arginine with a histidine (R228H), modifying the stereospecific properties of this region. These results add to the understanding of the genetic basis of Sjögren-Larsson syndrome and will be useful for DNA diagnosis of this disease.